Genetic gain and relationship of yield and yield attributes of mutant and cross-bred stevia (Stevia rebaudiana) genotypes - Suseno Amien; Haris Maulana; Dedi Ruswandi; Sarifah Nurjanah (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Amien S, Maulana H, Ruswandi D, Nurjanah S. 2021. Genetic gain and relationship of yield and yield attributes of mutant and cross-bred stevia (Stevia rebaudiana) genotypes. Biodiversitas 22: 3119-3126. Plant breeding programs involved many traits and genetic parameters in the selection process. The information on genetic parameters on yield and other related traits provided an overview for breeders and farmers in selecting new superior genotypes. The purpose of this study was to estimate genetic parameters including heritability and genetic gains in yield and other traits, to determine the relationship between various traits, and to select superior stevia (Stevia rebaudiana Bertoni) genotypes for each trait. Field experiments were carried out in two planting environments, namely, the highlands and the medium plains employing a randomized completed block design and each genotype was three replicates. The results showed that the yield had high heritability and genetic gains  ??in mutant populations, whereas cross-bred populations had moderate heritability and low genetic gains. Stem weight (SW) and number of leaves (NoL) traits were identified as having high heritability and genetic gains in both populations. The GT biplot measurement showed that the yield was identified to have a significant and positive correlation with SW (p<0.05). H4 was correlated with Number of branches (NoB), Yield, SW, and chlorophyll content (Chl) traits in the cross-bred populations. H9 excelled on and was correlated with NoL and plant height (PH). M11 was identified to be highly correlated with NoL, PH, NoB, and Chl traits in the mutant populations, while M15 excelled on and was correlated with yield and SW. The results of this study revealed that there was a potential for improvement in the traits tested of stevia through cross-bred and mutant populations in different environmental conditions. The selected genotypes can be developed in a suitable environment and used for further stevia plant breeding programs.